Evaluation of mixtures of acacia karroo leaf meal and setaria verticillata grass hay for indigenous Pedi goat production - Brown, David Adekunle (University of Limpopo, 2016)
Refer to document
Thesis (Ph.D. (Animal Nutrition)) -- University of Limpopo, 2016
Keywords: Acacia Karroo leaf; Setaria verticillata grass hay; Indegenous Pedi goat; Livestock -- Feeding and feeds; Goat breeds -- South Africa -- Limpopo; Dietary supplements